FinTech Services Delivery as Determinants of Customer’s Satisfaction: An Analysis of Banking Sector in Jordanian context - Alibraheem, Mohammad Haider (International Journal of Membrane Science and Technology, 2023)
With emerging literature on Financial Technology (Fintech) a number of research studies were conducted to analyse and look at the role of fintech services for the growth of several aspects in banking industry. But, limited studies attempted to consider an influence of Fintech services delivery improve the client satisfaction around Jordanian Banks. Thus, this study aims at examine how Fintech services provision improve of client satisfaction in Jordan’s Commercial Banks. A survey design that is cross-sectional design; where 600 questionnaires were personally distributed using convenience sampling technique. Statistical conclusions of this investigation showed Payment services, Accessibility to Fintech services (AC), Availability (AV), Transactionary costs (TC) Fintech service security (SS) to have positive significant influence upon Client’s Satisfaction (CS). The findings recommend technology financial facilities suppliers would advance upon this package and let system produce services distribution to attain consumers’ satisfaction at every stage. This study provides practitioners with important measures for evaluation of Fintech services effectiveness.